Effects of Cerebrolysin® in Patients With Minimally Conscious State After Stroke: An Observational Retrospective Clinical Study - Kim, Jun Yup; Kim, Hyun Jung; Choi, Hyo Seon; Park, So Young; Kim, Deog Young (Frontiers in Neurology, 2019)
Introduction: The neurotrophic drug Cerebrolysin is composed of low-molecular weight peptides and amino acids and has been shown to have neuroprotective and neuroplastic properties. Cerebrolysin has been reported to promote the recovery of motor functions in central nervous system disorders, however, the effects on the consciousness improvements in post-stroke patients have not yet been studied extensively. Therefore, we aimed to examine the effectiveness of Cerebrolysin on improving the consciousness level of stroke patients with minimally conscious state (MCS). Materials and Methods: In this retrospective study we included ischemic and/or hemorrhagic stroke patients with MCS according to the Coma Recovery Scale - Revised (CRS-R), who were admitted to our hospital between 2014 and 2017. All patients received comprehensive rehabilitation therapy including physical and occupational therapy. We compared patients treated with Cerebrolysin against patients who did not receive Cerebrolysin. Patients were included in the verum group if they received 10 mL Cerebrolysin IV for at least 20 days. CRS-R scores were assessed at admission and discharge. Results: Of 1531 patients screened, 75 were included in the study (Cerebrolysin, n=43; control, n=32). Baseline characteristics were similar between groups. At discharge, approximately two months after onset of stroke, Cerebrolysin-treated patients improved significantly in the CRS-R (p=0.010) after adjustment for confounders using linear mixed model, especially in the Oromotor (p=0.003) and Arousal subscales (p=0.038). No safety issues were observed. Conclusion: This retrospective study suggests that Cerebrolysin may improve the level of consciousness in stroke patients with MCS, which should be further investigated in a well-designed, double-blind, placebo-controlled, randomized trial.